Characteristics, enablers and barriers affecting entrepreneurial behaviour for academics in low- and middle-income countries: A scoping review. Issue 4 (4th July 2022) - Farrell, Alfred; Mapanga, Witness; Chitha, Nombulelo; Ashton, James; Joffe, Maureen
ABSTRACT: In the Fourth Industrial Revolution, academics should enhance entrepreneurial capacity to leverage digital-based advances and knowledge capital to support academic economic growth. A scoping review based on the Joanna Briggs Institute's guiding principles, using Krueger's intention-based entrepreneurship model as the theoretical framework, was undertaken to determine the extent of the literature related to characteristics, attributes, behaviours, enablers, and barriers of academic entrepreneurship in Higher Education Institutions in low- and middle-income countries (LMIC). Twenty articles were identified and included. The most common academic entrepreneurial characteristics included hunger for success, desire for independence, innovation, creativity, futuristic thinking, and self-esteem. For entrepreneurship to flourish, donor support, strong regulatory systems, political and macroeconomic stability were necessary. Characteristics such as innovation, creativity and futuristic thinking were tied to academic entrepreneurship. Further research on enablers and barriers is suggested to guide academics in LMIC universities with their transition to entrepreneurship as their engagement with society develops.